Dimensions of impulsivity related to psychopathic traits and homicidal behavior among incarcerated male youth offenders. (September 2021) - Maurer, J. Michael; Tirrell, Palmer S.; Anderson, Nathaniel E.; Rodriguez, Samantha N.; Caldwell, Michael F.; Van Rybroek, Gregory J.; Kiehl, Kent A.
Highlights: PCL:YV scores were significantly positively correlated with BIS-11 scores assessing attention deficits, self-control deficits, and cognitive complexity deficits. PCL:YV scores were not significantly correlated with BIS-11 scores assessing motor impulsivity deficits, perseverance deficits, or cognitive instability deficits. Secondary analyses suggest that youth who have previously committed homicide score higher on PCL:YV lifestyle/antisocial psychopathic traits and BIS-11 scores measuring non-planning impulsivity deficits compared to youth who have not committed homicide. Abstract: Despite impulsivity being included as scoring criteria within several measures of youth psychopathic traits, the relationship between psychopathic traits and dimensions of impulsivity among high-risk youth is not well-understood. Here we assessed psychopathic traits via total, factor, and facet scores from the Psychopathy Checklist: Youth Version (PCL:YV) and impulsivity through total, three-factor, and six-factor model scores from the Barratt Impulsiveness Scale (BIS-11) in incarcerated male youth offenders. Correlational analyses indicated PCL:YV total, Factor 2, Facet 3, and Facet 4 scores were significantly positively correlated with BIS-11 total scores. Additionally, psychopathy scores were significantly positively correlated with specific scores from the three-factor model of the BIS-11 (e.g. Motor and Non-Planning Impulsivity scores) and the six-factor model of the BIS-11 (e.g., Attention, Self-Control, and Cognitive Complexity Impulsivity scores). Secondary analyses suggest that participants who had previously committed homicide scored higher on lifestyle/antisocial psychopathic traits and specific dimensions of impulsivity (e.g., BIS-11 Non-Planning and Self-Control Impulsivity factor scores) compared to youth who had not previously committed homicide. Our results improve our understanding of the specific forms of impulsivity significantly correlated with youth psychopathic traits and how specific factors underlying both constructs potentially characterize youth associated with severe forms of antisocial behavior.